Relationships between gender, child temperament, parent-child relationship and behavior problems among preschool children in Kuala Lumpur - Yap, Ching Ching (2015)
The study aims to examine the relationships between gender, child temperament,parent-child relationship, and behavior problems (internalizing and externalizing problems) among preschool children in Kuala Lumpur. A total of 405 parents of private preschool children (mean age=5.18) were involved in the present study. They were selected by using multistage cluster sampling method. Child Behavior Checklist for Ages 1½-5 (CBCL/1½-5; Achenbach &Rescorla, 2000) Malay version, the Very Short Form of the Children’s Behavior Questionnaire (CBQ, Rothbart, 1996), and the Child-Parent Relationship Scale (CPRS; Pianta, 1992) were used to measure the key variables of the study. Univariate, bivariate and multivariate statistics were used in data analyses. Findings of the study showed that children with negative affectivity temperament had high internalizing and externalizing problems. Children with surgency temperament had higher externalizing problems whereas children with effortful control temperament tend to exhibit lesser externalizing problems. Conflicts in parent-child relationship were found to be positively correlated with internalizing and externalizing problems. Finding of the study also indicated a negative relationship between positive aspects of relationship and children’s externalizing problems. Negative affect and conflicts were significant predictors of internalizing problems. Externalizing problems was significantly predicted by conflicts, negative affect, effortful control, and surgency. Findings of the study also indicated that the conflicts in parent-child relationship had a moderation effect on the relationship between effortful control temperament and behavior problems. Children with high effortful control tend to exhibit more internalizing problems, especially when there is low conflict in parent-child relationship; whereas when there is high conflict in parent-child relationship, children with high effortful control tends to exhibit lesser externalizing problems. Lastly, the results revealed that the effect of negative affectivity temperament on externalizing problems was dependent on child’s gender. Findings imply that any efforts to enhance children’s behavior outcomes should possibly focus on the quality of parent-child relationship, especially for boys.